Application of integer linear program in optimizing convection sector production results using branch and bound method - Fery Firmansah; Muhammad Ridlo Yuwono; Fika Aisyah Munif (International Journal of Applied Mathematics, Sciences, and Technology for National Defense, 2023)
This study aimed to determine the application of the integer program in optimizing the production of the convection sector. Integer linear programming is a special form of linear programming in which the decision variable solutions are integers. Ayyumnah store as one part of the convection sectors with a home-scale does not have an appropriate strategy to optimize profits with limited materials owned. The method used in this study is an integer program with the branch and bound method. The result of this research is the optimal amount of production of long shirts and tunics at the Ayyumnah Store with maximum profit.